KOMITMEN TERHADAP PERUBAHAN DAN STRATEGI KOPING BERORIENTASI TUGAS DALAM KAITANNYA DENGAN KEPUASAN KERJA PEGAWAI - Sugita, I Ketut Adi; Supartha, Wayan Gede; Ardana, I Komang (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 7 Nomor 1 Tahun 2013)
Employee reaction to the organizational change is influenced by several psychological factors such as coping strategies and commitment to change. The purpose of this study was to test the effects of commitmentto changes and task-oriented coping strategies on job satisfaction. Respondents were taken from the total employee of ISI Denpasar, which numbered 139 people. Data was collected using questionnaire and were measured with Likert Scale. Data analysis techniques used univariate analysis of variance (One Way ANOVA). Based on research findings and the assessment of respondents’ commitment to changes there are two statements which have the category scores not good, then this should be a concern for the ISI Denpasar business success of the changes made. Employee job satisfaction high eventually will improve the performance of the optimal organization.
Keywords: commitment to change, coping strategy, job satisfaction